The Effect of Mobile Samsat Services and Drive-Thru Samsat Services on Motor Vehicle Tax Revenue at Samsat Soekarno Hatta, Bandung City - Muthmainah Muthmainah; Arimbi Triswastika; Adhita Arif Setyawan (Siber Nusantara of Economic and Finance Review, 2026)
Tax is one of the state revenues in Indonesia, one of which is Motor Vehicle Tax, which in its administration and management is the task of the Samsat office where in the office there are several programs including the mobile Samsat program and the drive-thru Samsat. This study aims to determine how influential the mobile Samsat and drive-thru Samsat programs are in tax revenue in the city of Bandung. The analysis method used in this study is Quantitative Descriptive which is analyzed first using the classical assumption test and then analyzed using multiple linear regression. It is concluded that the Mobile Samsat and Drive Thru Samsat partially and simultaneously where the results both have a significant influence on Motor Vehicle Tax Revenue at the Soekarno Hatta Samsat, Bandung City.